A giant retroperitoneal schwannoma in pregnancy: a rare case report and review of literature - Padhy, Aditya Prasad; Mishra, Prathmesh; Das, Deepak; Agarwal, Nishant (International Surgery Journal, 2020)
Retroperitoneal schwannomas are though more common among females, are very much rare tumors arising from sheath of nerves. Also, extremely rare during pregnancy. Very few articles till date are there regarding retroperitoneal schwannomas that’s too in pregnant female. Usually these are symptomatic unless causing some compression to other intra-abdominal structures like vessels or bowel and usually malignant. As its retroperitoneal very difficult to diagnose it. So, with proper investigations and radiological imaging, first have to find out the differential diagnosis prior to planning for surgery.